The Principle of Reversing the Burden of Proof in Money Laundering Crimes - Amrullah, Arief (Jurnal Cakrawala Hukum, 2023)
This article analyzes the principle of reversal of the burden of proof adopted in Article 77 and Article 78 of the Law. The purpose is to explain related to the principle of presumption of innocence (presumption of innocence), which has been adopted in Article 66 of the Code of Criminal Procedure. The normative legal research method examines authoritative texts as primary legal material and academic works as secondary legal material. The principle of reversal of the burden of proof in money laundering does not contradict the principle of presumption of innocence. On the contrary, the TPPU Law has placed defendants with legal subjects who deserve respect for their human rights to explain the origin of their assets not obtained from the proceeds of crime. The inability to explain the origin of the property does not make him guilty and criminalized. Because the Public Prosecutor is still obliged to prove his charges. How to cite item: Amrullah, M. Arief. â€œThe Principle of Reversing the Burden of Proof in Money Laundering Crimes.â€ Jurnal Cakrawala Hukum 14 no. 2 (2023):Â 146-154. DOI: doi.org/10.26905/idjch.v14i2.10813.